The Role of Loneliness and Self-Compassion as Predictors of Depressive Symptoms in College Students - Roselli Kezia Ausie; Kristi Poerwandari (Jurnal Psikologi, 2021)
High prevalence of depressive symptoms was found in college students. Loneliness, as one common problem incollege students, is assumed to have a role in the development of depressive symptoms. Earlier research foundself-compassion to be associated with better mental health. It is necessary to examine how loneliness and self-compassion play a role in the presence of depressive symptoms in college students. A total of 401 college studentsin the Jabodetabek area were involved in this research by completing online measurement instruments consistingof demographic questionnaire, 6-Item De Jong Gierveld Loneliness Scale, Self-Compassion Scale – Short Form,and Patient Health Questionnaire - 9. Data were analyzed using multiple regression analysis. Results showed thatloneliness had a significant role in predicting the increase in depressive symptoms, b = .374; t(392) = 7.68, p <.01, while self-compassion was able to predict the reduction of depressive symptoms in college students, b = -.353; t(392) = -7.15, p < .01. This study illustrates the importance of considering the quality of relationships anddeveloping self-compassion as an effort to reduce depression symptoms in college student